EFFECTS OF FLIPPED CLASSROOM ON STUDENTS’ ACADEMIC ACHIEVEMENT IN LEGAL ENGLISH LEARNING CONTEXT - Nhạc, Hương Thanh (LLT Journal: A Journal on Language and Language Teaching, 2021)
The primary focus of this study was to examine the effects of flipped classrooms on students’ academic achievement in legal English learning context at Hanoi Law University. To achieve the aim, fifty second-year students participating in the study were randomly divided into experimental and control groups. The experimental group was taught legal English with the flipped learning approach while traditional teaching method was applied to the control group. A pre-test and a post-test were administered to both groups to measure the impacts of flipped classrooms on students’ academic achievement in legal English. The results revealed that there were statistically significant differences in the means of the achievement test attributed to teaching methods in favour of the experimental groups. Also, survey questionnaires were administered to the students in the experimental group to identify their perceptions of the application of flipped classrooms on their legal English learning performance. The data showed that the majority of the students considered flipped classroom to be effective. It is hoped that the findings encourage instructors of English to use modern teaching strategies, in particular, flipped classroom strategy to improve the English teaching and learning process.